Library collaborative partnership of three O.P. Sienna Schools a gateway to O.P. Sienna Schools Library System - Delos Santos, Myra D.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
We are inexorably trapped in an era of change from a simple teaching and learning lifestyle to technologically invaded education that seemingly turns everything around overwhelmingly electronic Communications become synonymously equated to fast and instant delivery of information. In effect, educational institutions for their part will have to take an innovatory move to meet the complex demands of its clientele and its environment. The administrators, on the other hand, will have to strive to meet the standards of the new trend in the convergent modes of making the information resources available and the means provided to access these resources. Such standards are gained through new resolves of seeking competencies no longer in independence and rivalries but by partnership, collaboration and by all means, concerted efforts with other institutions. Thus, it is in this light that this study is focused on the Library collaborative partnership of three OP Siena Schools that will hopefully start the O.P. Siena Schools Library System. It is meant to build a collaborative endeavor of resource sharing among the sister-schools of the OP Siena Congregation where all schools are members and beneficiaries notwithstanding its individual's resource and financial contributory capability.
The research employed an experience and descriptive survey with the three OP Siena Schools in Luzon for sampling. It involved a total of 17 respondents where 13 are librarians and staff and 4 are IMC custodians and technicians. School librarians or representatives of other religious congregations administering similar network of schools and consortial institutions were also interviewed. All the data gathered were collated, studied and evaluated accordingly using frequency and ranking.
As a result, the collaborative practices among the three respondent institutions were identified and evaluated, their learning resources were conscientiously ascertained, and appraisal of their capabilities to form a collaborative partnership is attained. The study attests that the existing common activities among the librarians of the OP Siena Schools can serve as a take-off to materialize the collaborative efforts which are geared towards a wholesome support of each institution's curricula and instructions. All respondent LRCs have very rich collection of materials and equipment and well-trained manpower that through a systematic infrastructure and well-defined rules and policies of collaborative programs will not merely benefit its own clienteles but of the entire OP Siena Schools System. The respondents expressed readiness to support such innovative move and strongly recommended among others, interlibrary loan and bibliographic access through automation of the LRCs and electronic exchange of information on-line. Recommendations included budgetary concerns and maximum corroboration of the administration and its constituents.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: O.P. Sienna Schools Library System; Library cooperation -- Philippines; Library materials -- Philippines; Library administration -- Philippines